Teenage Mutant Ninja Turtles II the secret of the ooze - Propper, Gary.; Pressman, Michael; Gray, Thomas K.; Dawson, Kim.; Chan, David; Eastman, Kevin; Laird, Peter A.; Langen, Todd W.; Eastman, Kevin B.; Johnson, Shelly; Wright, John.; Mirkovich, Steve; et al. ([United States] : New Line Home Video, 2002)
The Teenage Mutant Ninja Turtles face a new challenge when a canister of the mutagen slime that transformed them fifteen years ago falls into the hands of their enemy the Shredder.
Based on characters created by Kevin Eastman and Peter Laird.
Director of photographer, Shelly Johnson ; edited by John Wright, Steve Mirkovich ; music, John Du Prez.
DVD.
Closed-captioned.
Keywords: Teenage Mutant Ninja Turtles (Fictitious characters) -- Drama; Feature films; Films for the hearing impaired